Analysis of doslidno-eksperimental’noy job performances on preparation of future specialists in industry of art to to artistically pedagogical to activity in out-of-school establishments of education (Pedagogy of Higher and Secondary Education, 2013)
Filatyeva Т. V. Analysis of doslidno-eksperimental’noy job performances on preparation of future specialists in industry of art to to artistically pedagogical to activity in out-of-school establishments of education.Doslidno-eksperimental’noy job which was conducted in more high artistically pedagogical educational establishments performances are summarized in the article. An author determines criteria and indexes of readiness to to artistically pedagogical to activity in out-of-school establishments of education, develops and inculcates the complex of diagonostichnikh in work.
Keywords: analysis; experimental work; out-of-school educational establishments; criteria and indexes of readiness; specialists in area of art